Out of the Qinghai-Tibetan plateau: Origin, evolution and historical biogeography of Morchella (both Elata and Esculenta clades) - Meng, Qing; Xie, Zhanling; Xu, Hongyan; Guo, Jing; Tang, Yongpeng; Ma, Ting; Peng, Qingqing; Wang, Bao; Mao, Yujing; Yan, Shangjin; Yang, Jiabao; Dong, Deyu; et al. (Frontiers in Microbiology, 2022)
Morchella has become a research hotspot because of its wide distribution, delicious taste, and phenotypic plasticity. The Qinghai-Tibet Plateau subkingdoms (QTPs) are known as the cradle of Ice age biodiversity. However, the diversity of Morchella in the QTPs has been poorly investigated, especially in phylogenetic diversity, origin, and biogeography. The genealogical concordance phylogenetic species recognition (GCPSR), differentiation time estimation and ancestral region reconstruction were used to infer Morchella's phylogenetic relationships and historical biogeography in the QTPs. Firstly, a total of 18 Morchella phylogenetic species are recognized in the QTPs, including 10 Elata clades and 8 Esculenta clades of 216 individuals. Secondly, the divergences of the 18 phylogenetic species were 50.24-4.20 Mya (Eocene- Pliocene), which was closely related to the geological activities in the QTPs. Furthermore, the ancestor of Morchella probably originated in the Northern regions (Qilian Shan, Elata cade) and southwestern regions(Shangri-La, Esculenta clade) of QTPs and might have migrated from North America (Ruforunnea clade) via Beringian Land Bridge (BLB) and Long-Distance Dispersal (LDD) expansions during the Late Cretaceous. Moreover, as the cradle of species origin and diversity, the fungi species in the QTPs have spread out and diffused to Eurasia and South Africa starting in the Paleogene Period. This is the first report that Esculenta and Elata clade of Morchella originated from the QTPs because of orogenic, and rapid differentiation of fungi is strongly linked to geological uplift movement and refuge in marginal areas of the QTPs. Our findings contribute to increasing the diversity of Morchella and offer more evidence for the origin theory of the QTPs.